Formation of reflexive skills as prevention of suicidal behavior in adolescents - N. Galiautdinova; S. Galyautdinova; L. Galyautdinova (European Psychiatry, 2022)
Introduction An important task of psychiatrists and psychologists is the prevention of suicidal behavior in adolescents.